Analisis Perbandingan Biaya Bahan Bakar Pada Boiler di PTm Ogawa Indonesia - Yuliani, Novita; Nurkhaerani, Fatma; Nugraha, Billy (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2025)
Industry is all forms of economic activity whose process is to change basic materials to produce products or finished goods that have added value or are beneficial to society. The purpose of this study is to identify the comparison of diesel fuel and natural gas costs in boilers at PT. Ogawa, to determine the efficiency value of natural gas fuel in boilers, and to determine the risks of using diesel fuel and natural gas. This study is a qualitative research, namely by interviewing employees in the Industry and Commercial sales division who are tasked with seeking information on prospective customers who will subscribe to gas from PGN. The results of the analysis obtained using literature studies are the average consumption of diesel fuel in boilers per month is 40,000 liters / month and estimated fuel costs of around Rp380,000,000, - / month, greater than the use of natural gas fuel of 42,350 m^3 / month and estimated fuel costs of around Rp229,108,000, - / month. So the use of natural gas fuel is superior compared to the use of diesel fuel